ANSIEDAD Y LOS ESTILOS DE AFRONTAMIENTO EN LOS ESTUDIANTES DE LA CARRERA DE PSICOLOGÍA EDUCATIVA DE LA UNIVERSIDAD NACIONAL DE CHIMBORAZO PERIODO ABRIL – AGOSTO 2019 - Guaman Paguay, William Marcelo (2020)
This research aims to determine the relationship between anxiety and coping styles of students in the seventh semester parallel A and B of the Educational Psychology degree at the National University of Chimborazo, anxiety is a repeated emotion that we perceive People sometimes in times of danger or worry. Anxiety helps us to have a domain in difficult instances, in addition the coping has been concretized as a set of cognitive and behavioral strategies that the person manages to specify internal or external demands that are perceived as excessive for the individual's resources. The research approach is quantitative, because of the level of research it is descriptive and correlational, the sample was of an intentional non-probabilistic type, with 58 students including 18 men and 40 women. The instruments for data collection were techniques and psychometric testing, the Beck Anxiety Inventory for the independent variable and for the dependent variable the Stress Coping Questionnaire, in addition to other resources such as the SPSS statistics 23 program for data analysis . Where it was found that there is a correlation between Anxiety and Coping Styles, that is, when the student has high levels of Anxiety, he presents different forms of coping with the daily circumstances that arise.